KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS ADVERSE DRUG REACTION REPORTING BY HEALTH CARE SERVICE PROVIDERS WORKING IN AIVEEN PHARMACIES WITHIN CENTRAL DIVISION KAMPALA DISTRICT. A CROSS SECTIONAL DESCRIPTIVE STUDY. - Kudye , Aaron (Student’s Journal of Health Research Africa, 2023)
Purpose of the study: The purpose of the study was to assess the adverse drug reaction reporting among healthcare service providers in Aiveen pharmacies Objectives of the study: The specific objectives of the study were; to determine the level of knowledge of reporting ADR“s among healthcare providers, to determine the attitude of reporting ADR“s and to determine the practices of reporting ADR“s among healthcare service providers in Aiveen pharmacies. Research methodology: The study employed the descriptive cross-sectional study to assess the specific objectives on a sample of 19 respondents using simple random sampling. Results of the study: From the study findings, 76.5% of respondents were not trained on drug safety and ADR reporting, 57.9% were not aware of national ADR reporting guidelines, 78.3% have never seen ADR reporting forms, 84.2% said reporting ADR“s is a professional obligation, 94.7% revealed reporting ADR“s benefit public health, 84.2% had positive attitude towards ADR reporting, 63.2% ever diagnosed on ADR, 78.9% have never reported ADR“s and 73.6% did not report ADR“s to any center neither to pharma- covigilance center, pharmaceutical company nor in hospital DTC and 63.0% revealed that there was lack of reporting forms. Conclusion: In conclusion, the research study clearly indicates a relatively better attitude but limited knowledge and practice toward ADRs reporting among healthcare professionals working in Aiveen pharmacies. Recommendation: The Ministry of Health through the National Pharmacovigilance and Medicine Information Centre (NPMIC) should create awareness of healthcare professionals through regular pieces of training, continuous education, and refresher courses in Pharmacovigilance and ADR reporting system. This training could be incorporated into the Continuous Professional Development (CPD) program for the doctors, nurses, and pharmacists as part of license requirements for the doctors, nurses, and pharmacists in Aiveen pharmacies.